La evolución del terrorismo de Al Qaeda al ISIS: organización, metodología y perfiles - Priego Moreno, Alberto (Razón y fe, 2019)
In the last 25 years international terrorism has evolved significantly. The emergence of al Qaeda was a real revolution since the methods, the goals and the organization were absolutely new. However, when we believed that we had defeated al Qaeda, the Islamic State was born, a much more lethal group that put Europe in its sights. Although it is true that both groups have similarities, they also present great differences, especially in terms of profiles.
Keywords: Al Qaeda; Islamic State; terrorism; profiles